PEMBELAJARAN BERBASIS HEAUTAGOGY DI ERA SOCIETY 5.0 - Tyas Talitha Majid; Novi Elvareta Permatasari Sihite; Muhammad Farelluddien; Rini Yuniar Purnama; Susan Febriantina; Nadya Fadillah Fidhyallah (Jurnal Pendidikan (Teori dan Praktik), 2023)
Abstract: to identify the learning system in era 5.0 by acquiring knowledge and skills effectively and efficiently in this kind of situation. society 5.0 brings a new era in various fields, especially education, this era produces an active, proactive and fun learning. Changes to learning have an impact on the learning process at all levels of education. In the heutagogi approach, it is defined as self-learning. This learning structure adheres to the principles of learning agency, metacognition and reflection. By using qualitative methods and a review of the literature, it can aim to give birth to a digitalization, the role and benefits of the education system in Indonesia in society 5.0 during the pandemic and after the pandemic which is carried out in distance learning and face-to-face with a heutagogi approach. Society 5.0 is an idea and concept that brings major changes in solving community problems by utilizing technology and taking into account human and humanities aspects. Keywords: education, heutagogi, technology, society 5.0, learning